2006
DOI: 10.1021/nl061081l
|View full text |Cite
|
Sign up to set email alerts
|

Defective Structure of BN Nanotubes:  From Single Vacancies to Dislocation Lines

Abstract: A combination of electron microscopy and theoretical calculations provides new insights into the structure, electronics, and energetics of point defects and vacancy lines in BN single-wall nanotubes (SWNT). We show that the point defects forming under electron irradiation in the BN SWNTs are primarily divacancies. Due to the partially ionic character of the BN bonding, divacancies behave like an associated Schottky pair, with a dissociation energy of around 8 eV. Clustering of multiple vacancies is energetical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
136
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(151 citation statements)
references
References 30 publications
13
136
2
Order By: Relevance
“…It was also found that, similar to the case of carbon nanotubes, 216,298 the energies are smaller for nanotubes with small diameters, 494,497 approaching the limit of a single BN sheet for large diameter nanotubes. 497 It was also found that the formation of DVs ͑note that the BN DV can be considered as an intimate vacancy pair example of a Schottky defect pair, i.e., a pair of oppositely charged defect centers͒ from two SVs is energetically favorable. 497 Moreover, once a vacancy forms, the formation energy for a subsequent neighboring vacancy is close to zero; thus the probability of forming a second neighboring vacancy is higher than at any other site.…”
Section: Theory Of Point Defects In Bn Nanotubesmentioning
confidence: 65%
See 2 more Smart Citations
“…It was also found that, similar to the case of carbon nanotubes, 216,298 the energies are smaller for nanotubes with small diameters, 494,497 approaching the limit of a single BN sheet for large diameter nanotubes. 497 It was also found that the formation of DVs ͑note that the BN DV can be considered as an intimate vacancy pair example of a Schottky defect pair, i.e., a pair of oppositely charged defect centers͒ from two SVs is energetically favorable. 497 Moreover, once a vacancy forms, the formation energy for a subsequent neighboring vacancy is close to zero; thus the probability of forming a second neighboring vacancy is higher than at any other site.…”
Section: Theory Of Point Defects In Bn Nanotubesmentioning
confidence: 65%
“…SW defects may also appear under large tension, as simulations 493 indicate. Thus the properties of point defects in BN nanosystems have been studied in a considerable body of theoretical papers 212,[494][495][496][497][498][499][500] within the framework of DFT.…”
Section: Theory Of Point Defects In Bn Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation
“…They can act as nucleation sites for the onset of deformation, when subjected to stress [2][3][4] . When exposed to chemical functional groups, defects can also behave as highly reactive sites and efficiently trap different molecules 5,6 .…”
mentioning
confidence: 99%
“…Graphene is an example of a 2D crystal, in which a dislocation glide can take place through Stone-Wales bond rotation 7,9,13,14 . Unlike graphene, MX 2 TMDs consist of metal (for example, M ¼ Mo, W, Nb and so on) atoms sandwiched by chalcogen atoms (for example, X ¼ S, Se, Te) establishing partial ionic bonds (see Supplementary Fig. 1).…”
mentioning
confidence: 99%